Full \(O(α)\) Electroweak Radiative Corrections to \(e^-e^+ → W^-W^+\) with Initial Beam Polarization Effects - Phan, Hong Khiem; Nguyen, Anh Thu; Nguyen, Huu Nghia (Communications in Physics, 2020)
We calculate full \(O(α)\) electroweak radiative corrections and \(O(α^3)\) initial state radiation (ISR) corrections to \(e^-e^+ → W^-W^+\) with initial beam polarization effects. In phenomenological results, we study the impact of electroweak and ISR corrections on cross-sections as well as their relevant distributions. We find that the corrections are order of 10% contributions. They are sizable contributions and should be taken into account at future lepton colliders